Correction of diffusion-weighted magnetic resonance imaging for brachytherapy of locally advanced cervical cancer. (August 2014) - Haack, Søren; Kallehauge, Jesper F.; Jespersen, Sune N.; Lindegaard, Jacob C.; Tanderup, Kari; Pedersen, Erik M.
Abstract Background. Geometrical distortion is a major obstacle for the use of echo planar diffusion-weighted magnetic resonance imaging (DW-MRI) in planning of radiotherapy. This study compares geometrical distortion correction methods of DW-MRI at time of brachytherapy (BT) in locally advanced cervical cancer patients. Material and methods. In total 21 examinations comprising DW-MRI, dual gradient echo (GRE) for B0 field map calculation and T2-weighted (T2W) fat-saturated MRI of eight patients with locally advanced cervical cancer were acquired during BT with a plastic tandem and ring applicator in situ. The ability of B0 field map correction (B0M) and deformable image registration (DIR) to correct DW-MRI geometric image distortion was compared to the non-corrected DW-MRI including evaluation of apparent diffusion coefficient (ADC) for the gross tumor volume (GTV). Results. Geometrical distortion correction decreased tandem displacement from 3.3 ± 0.9 mm (non-corrected) to 2.9 ± 1.0 mm (B0M) and 1.9 ± 0.6 mm (DIR), increased mean normalized cross-correlation from 0.69 ± 0.1 (non- corrected) to 0.70 ± 0.10 (B0M) and 0.77 ± 0.1 (DIR), and increased the Jaccard similarity coefficient from 0.72 ± 0.1 (non-corrected) to 0.73 ± 0.06 (B0M) and 0.77 ± 0.1 (DIR). For all parameters only DIR corrections were significant (p < 0.05). ADC of the GTV did not change significantly with either correction method. Conclusion. DIR significantly improved geometrical accuracy of DW-MRI, with remaining residual uncertainties of less than 2 mm, while no significant improvement was seen using B0 field map correction